Determination of micro-macro elements and heavy metals in carrots grown in turkey with faas - ERDOĞAN, GÜLBİN (My University, 2022)
In recent years, with the increase in environmental pollution, contamination in fruit, and vegetable production areas has become for human health. Our research has shown that the metal content of carrots produced in 3 different regions in Turkey and consumed by humans has never been compared between regions. Therefore, we aimed to compare Fe, Mn, Zn, Cu, Ca, K, Mg, Cr, Cd, Al, and Pb in carrots grown in these regions. Carrots were digested using the microwave-digestion method and the amount of these elements was measured by FAAS. According to the results, it was determined that there wasn’t Al, Cd, Mn, and Pb in carrot samples, but the presence of Cr, Fe, Zn, Cu, Ca, K, and Mg varied according to the regions. These values have been observed with the limit values determined by the WHO, Turkish Food Codex, and the Ministry of Agriculture and Forestry, that they are acceptable values. Considering the data on beneficial and harmful effects of the metals in the carrots grown in Turkey, it can be said that the heavy metal intake through carrots, does not pose an important risk to human health and they can be safely consumed.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; CHEMISTRY; MULTIDISCIPLINARY SCIENCES; Kimya (çeşitli); Genel Kimya; Multidisipliner; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Multidisciplinary; Physical Sciences